DAMPAK PENGUMUMAN KEMENANGAN DONALD TRUMP PADA PEMILU PRESIDEN AMERIKA SERIKAT 2016 ATAU “TRUMP EFFECT” TERHADAP ABNORMAL RETURN SAHAM LQ45 DI BEI - Ririn Wahyuni; Anny Widiasmara (INVENTORY: JURNAL AKUNTANSI, 2017)
This study is an event study that aims to find empirical evidence whether or not the reaction of the Indonesian capital market to one of the events abroad namely Donald Trump Victory Announcement Event as President of the United States 2016, using abnormal return indicator. This research is classified as research event study. The population in this study are all shares listed in LQ45 stock index in 2016. The sampling technique is purposive sampling, so that obtained the sample of 38 companies. Technique of collecting data using documentation method. Data analysis techniques used to answer this research hypothesis is paired-t test (paired sample t-test). The results of research at the level of significance of 5% indicates that there is a difference in average abnormal returns obtained by investors between before and after the events of Donald Trump Victory Announcement as President of the United States 2016. This is evidenced from the results of testing paired sample t test with a significance level of 0.000 Smaller than the specified significance level of 0.05. The results of this study prove that alternative hypothesis (Ha) is accepted. Key Terms: Abnormal Return, Trump Effect